(3GdUaGJ GdeeOhMI hGdePeheIs
(3ChdgG (B:s
(3jTJed Ydi WQa ef GdCNHGQ GdeeOhMI hGdePeheI aj GdUaGJ ef CTYGQ efJNHI eJdhI, hCOYjI eSehYI HCdaGX eJHhYIdJYjgG hJONdgG aj ecGJHJc hJSJYjf HgG aj eNGWHJc EPG NGWHJ s
(3BNQgG (B:s
(3WeSJ eYGde GdeYQha MJi cCf hLhOgG WdjJ HbGQ BNQ GdUaGJ GdeeOhMI hGdePeheI, hGdMeO ddg hMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ (B(3828) s
Keywords: (3GdCOHs